2019
DOI: 10.1039/c9cp02631b
|View full text |Cite
|
Sign up to set email alerts
|

Reactive nanomessengers for artificial chemical communication

Abstract: A non-synchronized artificial chemical communication system, based on a new modulation technique, namely reaction shift keying, is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The system designs from [2] and [9] were combined in [10] to implement long-range SMC based on reaction shift keying (RSK). To this end, two types of information molecules were employed, FCQDs and copper ions.…”
Section: Long-range Liquid-based Smcmentioning
confidence: 99%
See 2 more Smart Citations
“…The system designs from [2] and [9] were combined in [10] to implement long-range SMC based on reaction shift keying (RSK). To this end, two types of information molecules were employed, FCQDs and copper ions.…”
Section: Long-range Liquid-based Smcmentioning
confidence: 99%
“…The absorbance spectrum of the FCQDs, however, is unaltered by the presence of the copper ions. Exploiting this effect, FCQDs are used for synchronization of the Tx and the Rx by means of the absorbance signal in [10], while the copper ions are injected to modulate binary information onto the fluorescence signal. Consequently, the fluorescence signal is used for detection in [10].…”
Section: Long-range Liquid-based Smcmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome the limitation of non-synchrony between flow rate and timeslot, a useful modulation technique has been proposed — reaction shift keying (RSK). RSK implies that the transmitter emits the information particle in such a way that it undergoes the modification of a chemical-physical property by a reagent [ 8 , 9 ]. Therefore, the encoding of the symbol is obtained by means of the reaction condition.…”
Section: Modulation Techniquesmentioning
confidence: 99%
“…The name CDs, therefore, reflects the composition and property of emitting light at different wavelengths from the incident. Since their discovery by Xu et al in 2004, CDs have been applied for different basic research circumstances and very technical applications ranging from molecular communication to theranostics, as well as for the detection of specific analytes , with particular reference to metal ions. Moreover, as demonstrated by Sun et al, CD fluorescence yield is greatly increased through surface passivation . Although the chemical–physical mechanism underlying CD fluorescence is not yet fully understood, it is found in the literature that fluorescence can be modulated through several factors: particle size (quantum effect), surface groups, surface defects, and fluorophores with different degrees of π conjugation and electron holes located between the sp 2 carbons of the clusters and the sp 3 carbons of the matrices. Recent studies have shown that the optical properties vary considerably depending on the synthesis methodology used, passivation, doping, and size of the CDs. This suggests that fluorescence may depend on the surface of the nanoparticles, in particular on the ″surface defects″ that may be responsible for absorption at certain wavelengths .…”
Section: Introductionmentioning
confidence: 99%